Nubuatan Yehezkiel Tentang Kebangkitan Israel Dalam Perspektif Kristen Berdasarkan Yehezkiel 37:1-14 - Periman Jaya Lahagu; Sandra Rosiana Tapilaha (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The vision of passing from death to life is a glorious awakening. It is something that nature completely ignores, totally contrary to how it works (une privatione ad habitum non datur regressus-no way without ownership). Interestingly, the book of Ezekiel shows an unusual hope. In a valley full of human bones, God asked,